KONSEP PERLINDUNGAN DATA PRIBADI DALAM PENGAWASAN PEMILU TAHUN 2024 - Hilmi, Zaki (Bawaslu Provinsi Jawa Barat, 2022)
Personal Data Protection is normatively regulated in the provisions of Law Number 27 of 2022, with the enactment of these provisions it should be a solution to problems that arise in the election oversight process, especially the election law enforcement process. The concept of personal data protection is important, especially with regard to Supervision of the Registration and Verification Stages of Election Contestants, Compilation of Voter Lists and Voting. In this stage it is closely related to the privacy of personal data and the personal dignity of a person to hold information and how this information is used. With the enactment of the concept of personal data protection in election supervision, it should be able to strengthen the position of election supervisors in preparing more technical legal instruments to prevent and deal with alleged election violations.